Laboratory Evaluation of Aging Behaviour of SBS Modified Asphalt - Jie Wang; Yongchun Qin; Songchang Huang; Jian Xu (Advances in Materials Science and Engineering)
To study the effect of aging SBS modified asphalt on the performance of asphalt pavement, aging at various times and temperatures was conducted with thin film oven, and then tests were made about the penetration, softening point, ductility, viscosity, toughness, and fluorescence microscopy of modified asphalt with different aging levels. The results show that, with the increasing of aging time, the penetration and ductility of modified asphalt decrease while its softening point and viscosity increase, and the variation trend of the toughness and tenacity is related to the aging temperature; the aging dynamic model with viscosity as parameter can well characterize the aging process of modified asphalt; at microlevel, with the decreasing of SBS particle size, the uniformity of particle size is better. Analysis of macroscopic properties, microscopic characteristics, and significance shows that the SBS particle area ratio has a significant correlation with tenacity as the aging temperature changes. When the aging temperature is 163°C, the SBS particle area ratio still has a significant correlation with tenacity as the aging time changes.